Inside Cover: An Efficient Synthesis of Porphyrins with Different meso Substituents that Avoids Scrambling in Aqueous Media (Chem. Eur. J. 4/2015). Issue 4 (19th January 2015) - Nowak‐Król, Agnieszka; Plamont, Rémi; Canard, Gabriel; Edzang, Judicaelle Andeme; Gryko, Daniel T.; Balaban, Teodor Silviu
<x xml:space="preserve">Abstract</x> A long‐standing problem in the synthesis of A3B‐, A2B2‐, or AB2C‐porphyrins, the scrambling of the intermediate porphyrinogens formed by the condensation of pyrrole with at least two different aldehydes, has now been circumvented by using an environmentally friendly experimental procedure. T. S. Balaban, D. T. Gryko and their co‐workers describe in the Full Paper on page 1488 ff. the optimization of a water‐based synthesis using either EtOH or THF as co‐solvent and HCl as the catalyst. This procedure was discovered independently in Marseille and Warsaw for both meso‐arylporphyrins, which are usually purple, or meso‐arylethynylporphyrins, which, due to the extended π system, are green and have potential applications such as in nonlinear optics or photodynamic therapy.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>